Money, interest, and capital accumulation in Karl Marx's economics: A monetary interpretation - Eckhard Hein (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2002)
Starting from Schumpeter.s important distinction between .real analysis. and .monetary analysis., in this paper it is shown that major elements of Marx.s economic theory fall in the camp of monetary analysis and the implications for Marx.s theory of capital accumulation are derived. First, Marx.s theory of labour value has to be considered a .monetary theory of value. because .abstract labour. as the social substance of value cannot be measured without a social standard of value. Money as a social representative of value, therefore, is introduced at the very beginning of Marx.s microeconomics. Marx.s rejection of Ricardo.s interpretation of Say.s Law requires that money as a means of circulation and as a means of payment is nonreproducible and therefore cannot be a commodity. Second, in the schemes of reproduction it becomes clear, that the realisation of profits for the capitalist class as a whole requires money advances, which have to increase by means of rising credit in a growing economy. Third, the rate of interest in Marx.s economics is conceived of as a monetary category determined by relative powers of financial and industrial capitalists. Therefore, similar to post-Keynesian theories of distribution and growth, the rate of capital accumulation is determined by the expected rate of profit and the exogenous rate of interest. From this it follows, that any .real theory. of crisis and stagnation, as the falling rate of profit theory of crisis, cannot be sustained within Marx.s monetary analysis.
Keywords: B14; B24; E11; 330; Money; interest; capital accumulation; Marx's economics; Sozialistische Wirtschaftstheorie; Marxistische Arbeitstheorie; Geldtheorie; Zins; Postkeynesianismus; Theorie